The Art of the Accident: Art+Architecture+media technology - Brouwer, Joke; Mulder, Arjen (Amsterdam NAI Publishers, 1998)
Failure and malfunction are inherent in all technological products. In The Art of the Accident, the concept of ?accident? contains not just the idea that each machine brings with it its own form of disaster but also the suggestion that in a world of network technologies the old distinction between timeless form and time-dependent processes is becoming increasingly unclear.Ars accidentalis recognizes the creative potential of the accident, the fall, and the instability of digital media. The book maps the transformation of space, time bodies, machines and architectures through the conceptual and noninstrumental use of the computer.The Art of the Accident includes essays and interviews from composer Dick Raaymakers, biologist Humberto Maturana, urbanist Paul Virilio, literary scientist Katherine Hayles, endophysicist Otto Rössler and computer scientist Steve Mann. It also contains a series of artistic interventions by people such as Knowbotic Research, Perry Hoberman and Diller Scofidio. This fully illustrated book takes a synthesizing approach towards intersecting practices in art and science, outlining the basics of an ars accidentalis